Ionization of Helium by neutronic impact. (July 2015) - Ambrosio, M J; Mitnik, D M; Gasaneo, G; Colavecchia, F D
Synopsis: We present fully differentiated cross sections for the Helium double ionization by neutronic impact. From our theoretical results we observe the underlying mechanisms that lead to the breakup of the target.